Symptoms of the Planetary Condition A Critical Vocabulary - Bunz, Mercedes; Mara Kaiser, Birgit; Thiele, Kathrin (meson press, 2017)
This book explores the future of critique in view of our planetary condition. How are we to intervene in contemporary constellations of finance capitalism; climate change and neoliberalism? Think we must! To get to the symptoms; the book's 38 terms ranging from affect and affirmation to world and work provide the reader with a critical toolbox to be continued. Negativity; judgment and opposition as modes of critique have run out of steam. Critique as an attitude and a manner of enquiry has not.